Mongol Empire - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Surviving history., 2021)
Provides a series of questions that ask the reader to consider their life and choices as both a soldier and citizen of the Mongol Empire. Discusses what daily life was like for individuals and soldiers, various diseases and famines, and how lands were conquered. Includes illustrations, sidebars, resources for further study, and a glossary.